THE PROBLEM OF ANTIBIOTIC RESISTANCE AND ITS IMPACT ON DENTISTRY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Antibiotic resistance is a growing problem in dentistry, as empirical therapy and improper use are leading to an increase in the population of resistant microorganisms in the oral cavity. Studies show that 30-40% of antibiotic prescriptions in dental practice are prescribed without indication. 25-35% of Streptococcus spp. are resistant to penicillin, and 40% of Prevotella species are resistant to beta-lactams. This situation reduces the effectiveness of the treatment of odontogenic infections, periodontitis and peri-implantitis. To solve the problem, it is recommended to adhere to the principles of rational antibiotic therapy, conduct microbiological diagnostics, use local antiseptics and alternative therapy methods. This approach allows to reduce the consumption of antibiotics by 35-40% and prevent the development of resistance.